Procedural Audio in Computer Games Using Motion Controllers: An Evaluation on the Effect and Perception. (23rd December 2013) - Böttcher, Niels; Martínez, Héctor P.; Serafin, Stefania
Abstract : A study has been conducted into whether the use of procedural audio affects players in computer games using motion controllers. It was investigated whether or not (1) players perceive a difference between detailed and interactive procedural audio and prerecorded audio, (2) the use of procedural audio affects their motor-behavior, and (3) procedural audio affects their perception of control. Three experimental surveys were devised, two consisting of game sessions and the third consisting of watching videos of gameplay. A skiing game controlled by a Nintendo Wii balance board and a sword-fighting game controlled by a Wii remote were implemented with two versions of sound, one sample based and the other procedural based. The procedural models were designed using a perceptual approach and by alternative combinations of well-known synthesis techniques. The experimental results showed that, when being actively involved in playing or purely observing a video recording of a game, the majority of participants did not notice any difference in sound. Additionally, it was not possible to show that the use of procedural audio caused any consistent change in the motor behavior. In the skiing experiment, a portion of players perceived the control of the procedural version as being more sensitive.